Assessing properties of solar-dried banana with white chocolate coating - Warsiki Endang; Hanniyah Chairunnisah Putri; Suparno Ono; Taksaudom Nuraemon; Rardniyom Chananpat (BIO Web of Conferences)
Banana is one of the most prevalent tropical fruits, renowned for its nutritional and energetic value. Drying bananas prolongs their shelf life, reduces weight, conserves storage space, and controls enzymatic reactions that lead to banana degradation. Drying also enhances sensory attributes such as flavor and texture. Producing solar-dried banana coating with fancy flavors is an innovation in banana product processing, especially with white chocolate coating. However, the coating made from white chocolate mixed with various flavors has a problem with its viscosity, and this type of chocolate is considered not heat resistant enough, leading to melting in most tropical temperatures, such as those in Thailand. Therefore, four components were incorporated into the mixture of white chocolate coating to improve its quality. Palm Kernel Oil (PKO), Palmitic Acid (PA), Cocoa Butter (CB), and Soy Lecithin (SL) were added to enhance the coating's properties. The results showed that CB had the best viscosity at 9600 cP, a slightly lower melting point at 29.01°C, and a hardness measurement of 152 g. These modifications proved proper components to stabilize the coating under high temperatures, making it suitable for tropical climates. Further research is needed to produce a heat-resistant white chocolate coating, ensuring it maintains its integrity and desirable properties during storage and transportation in hot conditions. Additionally, consumer preferences and sensory evaluations must be considered to ensure that the modified white chocolate coating meets taste and texture expectations while providing the necessary heat resistance.